Peningkatan Hasil Belajar Teknik Dasar Passing Atas Permainan Bola Voli Melalui Tutor Sebaya : Penelitian - Deden Hermawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The process of learning basic techniques of mini volleyball at the elementary school level still faces several obstacles. One of the challenges encountered is the lack of mastery of the basic overhead passing technique. The use of less engaging teaching methods results in students being less motivated to learn the fundamental overhead passing technique in volleyball. The objective of this research is to determine the impact of peer tutoring methods on students' abilities in learning mini volleyball, describe the implementation of peer tutoring methods in mini volleyball learning, and assess the improvement in physical education learning outcomes regarding the basic overhead passing technique through peer tutoring. This study is a classroom action research utilizing multiple data sources. The data sources include students' learning outcomes in the basic overhead passing technique, teacher activity records, and student engagement levels. The research findings indicate that peer tutoring facilitates students in performing overhead passing movements more effectively. Peer assistance makes the learning process dynamic and enjoyable, leading to increased student confidence and active participation in learning activities. The results of students' overhead passing skills showed improvement, as seen in the second cycle of learning, which recorded higher scores compared to the initial conditions. Peer tutoring can enhance learning outcomes for fundamental volleyball passing movements.